2016
DOI: 10.1177/0218492316629281
|View full text |Cite
|
Sign up to set email alerts
|

Effect of decortication and pleurectomy in chronic empyema patients

Abstract: Decortication and pleurectomy via a posterolateral thoracotomy significantly improves pulmonary function and chest wall diameters in patients with chronic empyema due to tuberculosis or other diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 20 publications
3
8
0
1
Order By: Relevance
“…A significant improvement in follow-up pulmonary function test values was observed compared with preoperative values (p < 0.001) as in Table 5. The observed change was comparable with a previous study [14].…”
Section: Commentsupporting
confidence: 92%
“…A significant improvement in follow-up pulmonary function test values was observed compared with preoperative values (p < 0.001) as in Table 5. The observed change was comparable with a previous study [14].…”
Section: Commentsupporting
confidence: 92%
“…pulmonary functions significantly 4,[11][12][13] . Bagheri et al 4 studied 50 cases with chronic empyema and performed posterolateral thoracotomy in all patients. He pointed out that both FEV1 and FVC improved significantly after the operation.…”
Section: Discussionmentioning
confidence: 96%
“…Thickened pleura causes decreased thoracic wall compliance and even thoracic deformity. The fundamentals of the treatment are to remove the cortex on the parenchyma to provide the lung to re-expand and to remove the thickened pleura to provide the chest wall its mobility, especially relieve the diaphragm to be able to contract again 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Along with the PO‐LOS, we wanted to analyze other clinical indicators of the procedure performance. The reduction in thoracic volume has been considered as a measure of lung function and chest mobility impairment due to pleural infection 24–26 . Both studies of Bagheri et al 25 and Gokce et al 24 reported an enlargement of the hemithorax diameters after full decortication of the lung for Stage 3 empyema.…”
Section: Discussionmentioning
confidence: 99%